2020
DOI: 10.3390/app10062169
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Integrity Analysis of a Printed Circuit Heat Exchanger with Channel Misalignment

Abstract: Printed circuit heat exchangers (PCHEs), which are used for thermal heat storage and power generation, are often subject to severe pressure and temperature differences between primary and secondary channels, which causes mechanical integrity problems. PCHE operation may result in discontinuity, such as channel misalignment, due to non-uniform thermal fields in the diffusion bonding process. The present paper analyzes the mechanical integrity, including the utilization factors of stress and deformation under va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…Armanto and Lee conducted a study about the mechanical integrity analysis of a PCHE with channel misalignment. This study also shows high-stress intensity at the tip edge of PCHE channels [13]. The phenomenon where the stress is shown high at the tip has also been observed at the nanoscale.…”
Section: Introductionsupporting
confidence: 76%
“…Armanto and Lee conducted a study about the mechanical integrity analysis of a PCHE with channel misalignment. This study also shows high-stress intensity at the tip edge of PCHE channels [13]. The phenomenon where the stress is shown high at the tip has also been observed at the nanoscale.…”
Section: Introductionsupporting
confidence: 76%
“…The mechanical integrity of the PCHE with the considered channel geometry is verified as in ref. [48].…”
Section: Pche Recuperator Design Methodologymentioning
confidence: 99%
“…When pressure and temperature differences between PCHE channels are too large, it is easy to cause channel dispatching. The stress deviation of the main PCHE channels in the power generation system was studied by Simanjuntak et al [14] when the pressure difference between the PCHE channels was 19.5 Mpa and the temperature difference was 25 • C. The result showed that the stress intensity grew with the increase in misalignment. It is less safe than the condition without misalignment.…”
Section: Introductionmentioning
confidence: 99%